Orbitofrontal sulcogyral morphology in patients with cocaine use disorder. (30th November 2020) - Patti, Marisa A; Wochele, Sarah; Hu, Yirui; Regier, Paul S.; Childress, Anna Rose; Troiani, Vanessa
Highlights: Atypical sulcual patterns in orbitofrontal cortex are identified in psychopathology. Substance use disorders commonly co-occur with psychopathology. Sulcogyral patterns frequencies did not differ between cocaine use and controls. H-shaped sulcogyral pattern subtypes exist within main pattern classifications. Larger variations in sulcogyral pattern subtypes were found in cocaine use disorder. Abstract: Orbitofrontal cortex (OFC) is thought to be involved in appropriate processing of rewarding stimuli, and abnormal OFC structure and function has been found in patients with substance use disorders. Atypical patterns of the H-sulcus in the OFC have been primarily identified with schizophrenia, but also with bipolar disorder, both of which are associated with comorbid substance use. Given the high rates of substance use within Axis I psychiatric disorders, it is reasonable to consider how frequencies of OFC patterns in populations with only substance use compare to controls. This information is crucial to disentangle whether atypical frequencies of H-sulcus sulcogyral patterns within psychopathology are associated with the psychiatric or substance use phenotype. Here, we present the first analysis of H-sulcus sulcogyral patterns in a population of adult black men with ( n   =   84 ) and without ( n   =   24 ) cocaine use disorder (CUD). We find that OFC sulcogyral patterns are not significantly different from the control group, indicating that OFC sulcogyral patterns are not disrupted in patients with CUD. As exploratory analyses, we describe OFC sulcogyral pattern subtypes in this cohort as well as an additional control group ( n   =   52 ), in order to add to the growing body of literature on OFC sulcogyral pattern characterization.